Combat full-thickness macular hole due to high-intensity light exposure - Уманець, Микола Миколайович; Чумаков, Євген Андрійович (My University, 2025)
We present a challenging unique case of a soldier with a macular hole induced by high-intensity light exposure after gazing at the spotlight of the air-defense system, which was treated with vitrectomy and internal limiting membrane (ILM) double flap. The macular hole was visualized and diagnosed using optical coherence tomography (OCT). The surgery invovled 25-G vitrectomy, ILM double flap, and intraocular gas endotamponade (15% perfluoropropane) with postoperative face-down positioning. The best-corrected visual acuity (BCVA) at admission was 0.12 eccentric. The OCT showed the full-thickness macular hole with a 534-μm diameter. After uneventful surgery, macular hole was closed, achieving postoperative BCVA of 0.25 at 1 month. Hence, we demonstrate that although rarely, even brief high-intensity light exposure can cause full-thickness macular hole. Such a case was successfully managed with vitrectomy and ILM double flap technique. Consequently, wearing protective equipment during potential light exposure by military personnel is essential to prevent such injuries.